P2RX7 Purinoceptor as a Therapeutic Target—The Second Coming? - Young, Chris N. J.; Górecki, Dariusz C. (Frontiers in Chemistry, 2018)
The P2RX7 receptor is a unique member of a family of extracellular ATP (eATP)-gated ion channels expressed in immune cells, where its activation triggers the inflammatory cascade. Therefore, P2RX7 has been long investigated as a target in the treatment of infectious and inflammatory diseases. Subsequently, P2RX7 signalling has been documented in other physiological and pathological processes including pain, CNS and psychiatric disorders and cancer. As a result, a range of P2RX7 antagonists have been developed and trialled. Interestingly, the recent crystallization of mammalian and chicken receptors revealed that most widely-used antagonists bind a unique allosteric site. The availability of crystal structures allows rational design of improved antagonists and modelling of binding sites of the known or presumed inhibitors. However, several unanswered questions limit the cogent development of P2RX7 therapies. Firstly, this receptor functions as an ion channel, but its chronic stimulation by high eATP causes opening of the non-selective large pore (LP), which can trigger cell death. Not only the molecular mechanism of LP opening is unknown but its function(s) are unclear. Furthermore, how can tumour cells take advantage of P2RX7 for growth and spread and yet survive overexpression of potentially cytotoxic LP in the eATP-rich environment? The recent discovery of the feedback loop, wherein the LP-evoked release of active MMP-2 triggers the receptor cleavage, provided one explanation. Another mechanism might be that of cancer cells expressing a structurally altered P2RX7 receptor, devoid of the LP function. Exploiting such mechanisms should lead to the development of new, less toxic anticancer treatments. Notably, targeted inhibition of P2RX7 is crucial as its global blockade reduces the immune and inflammatory responses, which have important anti-tumour effects in some types of malignancies. Therefore, another novel approach is the synthesis of tissue/cell specific P2RX7 antagonists. Progress has been aided by the development of p2rx7 knockout mice and new conditional knock-in and knock-out models are being created. In this review, we seek to summarise the recent advances in our understanding of molecular mechanisms of receptor activation and inhibition, which cause its re-emergence as an important therapeutic target. We also highlight the key difficulties affecting this development.